Estimation of groundwater recharge response from rainfall events in a semi-arid fractured aquifer: Case study of quaternary catchment A91H, Limpopo Province, South Africa. Issue 1 (1st January 2019) - Nemaxwi, P.; Odiyo, J.O.; Makungo, R.
Abstract: This study estimated groundwater recharge response from rainfall events in a semi-arid fractured aquifer. This is crucial as recharge response has an influence on available groundwater in an aquifer. Groundwater levels were modelled and used to evaluate the response of groundwater recharge from rainfall events using Extended model for Aquifer Recharge and soil moisture Transport through unsaturated Hard rock (EARTH) model. Chloride Mass Balance (CMB) method was also used to estimate groundwater recharge in quaternary catchment A91H. Calculated local recharge using CMB method was interpolated in ARCGIS to generate groundwater recharge distribution maps. Estimated local recharge using CMB method ranged from 0.24 to 8.8 mm/a (0.04–1.3% mean annual precipitation (MAP)). Estimated recharge using EARTH model ranged from 3 to 10.3% of 656 mm of MAP. The average recharge was 6.12% of the MAP, equivalent to 40.1 mm/a. EARTH model and CMB method yielded results which were found to be in the same ranges to those obtained from other studies. Rapid—intermediate recharge response mechanism was identified in the study. The results confirmed and expanded knowledge on the nature of groundwater recharge response from rainfall in fractured aquifers in semi-arid areas and the applicability of EARTH model and CMB method in recharge estimation.